"[M]ost plain, rational, and easie": Rhetorical Disavowal in Early Eighteenth-Century Inoculation Pamphlets. Issue 2 (3rd April 2018) - McGuire, Kelly
Abstract : In the second decade of the eighteenth century, English physicians mobilized a rapidly expanding print culture to launch themselves into the thick of public debate with sharply worded pamphlets defending and denouncing the newly introduced practice of inoculation (the less effective forerunner of vaccination). This paper explores the new kind of medical rhetoric that flourished in the midst of this controversy, one that downplays medical authority and even disavows its own rhetorical character, much like the vaccination debates of today.